Tissue reactions to a component of root canal system bacteria: lipoteichoic acid - Costa Junior Edson Dias; Souza-Filho Francisco José de; Barbosa Sérgio Valmor (Fundação Odontológica de Ribeirão Preto, 2003)
Lipoteichoic acid (LTA), present in Gram-positive microorganisms, has physiochemical characteristics that allow it to act as an immunogen. Due to polymicrobial characteristics of root canal infections, LTA can participate in the development of periapical disease. The reaction of the rat subcutaneous tissue to Teflon tube implants, filled with Fibrinol soaked in lipoteichoic acid (concentration of 150 µg/ml), was observed. Lipoteichoic acid provoked an inflammatory tissue reaction.